The causal relationship between psoriasis and cancers: a two-sample Mendelian randomization analysis - Long, Jiaye; Yang, Miyang; Pang, Yingrong; Kang, Hongyan; Liang, Shuai; Wang, Du (Frontiers in Oncology, 2024)
Background: Although observational studies suggest a correlation between psoriasis (PS) and cancers, it is still unknown whether this association can replace causal relationships due to the limitations of observational studies. Therefore, we conducted a two-sample Mendelian randomization (MR) analysis to evaluate the causal relationship between PS and cancers.Methods: PS genetic summary data were obtained from two genome-wide association studies (GWAS). We employed MR Base for individuals retrieving tumors from distinct locations. Inversevariance weighted analysis was the principal method used for MR, supplemented by weighted median, MR Egger, simple mode, and weighted mode. To investigate the possible link between psoriasis and cancers, we performed two independent two-sample MR studies and a meta-analysis based on two independent MR analyses.Results: Two independent MR analyses both found no significant causal relationship between PS and overall cancers (OR=1.0000, 95% confidence interval [CI]:0.9999-1.0001, P=0.984; OR=1.0000, 95% CI:0.9999-1.0001, P=0.761), and no significant causal relationship with 17 site-specific cancers. In the meta-analysis conducted by two two-sample MR analyses, there was no significant causal relationship between PS and overall cancers (OR=1.0000, 95% CI: 0.9999-1.0001, P=1.00, I 2 =0.0%), and there was no significant causal relationship with 17 site-specific cancers. Conclusion: Our findings do not support a genetic link between PS and cancers. More populationbased and experimental investigations will be required better to understand the complicated relationship between PS and cancers.